2021
DOI: 10.1037/pro0000365
|View full text |Cite
|
Sign up to set email alerts
|

Help-seeking for depression as a stigmatized threat to masculinity.

Abstract: To better understand men's reluctance to seek help for mental health issues, we investigated the contributions of depression, stigma, and masculinity on help-seeking likelihood in a sample of depressed men. Two-hundred and fifty-eight men, who screened positive for depression on the PHQ-2, completed measures assessing self-stigma, self-reliance, emotional control, and general help-seeking likelihood via an online Qualtrics survey. Path analysis using MPlus tested one model of moderated mediation and two mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 48 publications
0
28
1
Order By: Relevance
“…The prevailing narrative in academic and dominant social discourse portrays men as reluctant to seek mental health care for fear of being seen as weak 22 . Commonly implicated in explaining this reticence are psychosocial barriers including the perception of mental health care as emasculating or feminine 2,23 . That 40% of respondents in the current study initiated their own help‐seeking counters this long standing narrative, adding empirical weight to contemporary research showing that men's uptake of professional services is increasing 1,24 .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The prevailing narrative in academic and dominant social discourse portrays men as reluctant to seek mental health care for fear of being seen as weak 22 . Commonly implicated in explaining this reticence are psychosocial barriers including the perception of mental health care as emasculating or feminine 2,23 . That 40% of respondents in the current study initiated their own help‐seeking counters this long standing narrative, adding empirical weight to contemporary research showing that men's uptake of professional services is increasing 1,24 .…”
Section: Discussionmentioning
confidence: 58%
“…22 Commonly implicated in explaining this reticence are psychosocial barriers including the perception of mental health care as emasculating or feminine. 2,23 That 40% of respondents in the current study initiated their own help-seeking counters this long standing narrative, adding empirical weight to contemporary research showing that men's uptake of professional services is increasing. 1,24 A myriad of factors could explain this increase, including greater allocation of government funding to mental health services, alongside targeted public health initiatives aiming to normalise men's help-seeking.…”
Section: Pathways To and Recommendations For Helpseekingmentioning
confidence: 65%
“…Equally alarming is the extremely low utilization rate of mental health services among this study population and the relatively low interest in using mental health services. Studies have reported that individuals experiencing a mental condition such as depression are not likely to seek help due to stigmatization and fear for discrimination [ 43 45 ]. Due to the lack of resources or lack of help-seeking behaviour, these individuals might not receive the necessary intervention to address their depression [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though such mental health challenges can prompt men’s help-seeking, there is much debate about the role of masculinity in men’s use of professional mental health care services (Seidler et al, 2018). In gendered contexts, masculine norms and ideals—most prominently self-reliance—have featured as a pivot that can constrain (Addis & Mahalik, 2003; Mahalik & Di Bianca, 2021; Pirkis et al, 2017) or enable (Struszczyk et al, 2019) men’s engagement with professional mental health care. Herein, the predominance of professional mental health care services as what legitimately counts as the help has also limited depictions of, and insights to men’s mental health help-seeking (Fletcher & St George, 2010; Harding & Fox, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Self-reliance and suicidal thoughts have also been coupled to explain why men are unlikely to talk through problems or seek help from friends and family when feeling down or vulnerable (Pirkis et al, 2017). When depression threatens men, Mahalik and Di Bianca (2021) further suggest self-reliance is levered by men to re-establish their manhood. Qualitative work has consistently challenged these deficit depictions of self-reliance, contextualizing how a plurality of masculinities can be embodied to work for men’s mental health help-seeking (Emslie et al, 2006; Ferlatte et al, 2019; Oliffe et al, 2021; Player et al, 2015).…”
Section: Introductionmentioning
confidence: 99%